The Plantlia: free android app for measurement of foliar area and color with automated scaling - Ovidio Valerio-Cubillo (Tecnología en Marcha)
There is a plethora of apps available for different biological applications, however, mobile software for plant measurement, specifically for field conditions are limited. Additionally, there is a need to create large training datasets for machine learning applications. A free app called Plantlia, which is available to download from the Google Play Store, aims to resolve this with an intuitive interface, and a method to automatically scale images using homography. Plantlia also includes methods to share results from either direct measurements or thresholded images. This paper aims to describe some of the functions of Plantlia, as well as show scenarios that display its performance. Images from cellphones and drone pictures were used for validation on different devices. This is important, as it means that users with low-cost equipment, like drones with no GPS information, can still analyze localized field information. Similarly, researchers can do communal efforts to share and receive in-field data to create machine learning datasets.